Characterization of Treponema denticola Mutants Defective in the Major Antigenic Proteins, Msp and TmpC - Abiko, Yuki; Nagano, Keiji; Yoshida, Yasuo; Yoshimura, Fuminobu (PLOS ONE, 2014)
Treponema denticola, a gram-negative and anaerobic spirochete, is associated with advancing severity of chronic periodontitis. In this study, we confirmed that two major antigenic proteinswere Msp and TmpC, and examined their physiological and pathological roles using gene-deletion mutants. Msp formed a large complex that localized to the outer membrane, while TmpC existed as a monomer and largely localized to the inner membrane. However, TmpC was also detected in the outer membrane fraction, but its cell-surface exposure was not detected. Msp defects increased cell-surface hydrophobicity and secretion of TNF-α from macrophage-like cells, whereas TmpC defects decreased autoagglutination and chymotrypsin-like protease activities. Both mutants adhered to gingival epithelial cells similarly to the wild-type and showed slightly decreased motility. In addition, in Msp-defective mutants, the TDE1072 protein, which is a major membrane protein, was abolished; therefore, phenotypic changes in the mutant can be, at least in part, attributed to the loss of the TDE1072 protein. Thus, the major antigenic proteins, Msp and TmpC, have significant and diverse impacts on the characteristics of T. denticola, especially cell surface properties.